The (Non-)Orthodox Tradition, the (Non-)Orthodox Everydayness (KULT_online, 2018)
What is the relation between the Christian Orthodox tradition and people’s everyday lives? The volume, Praying with the Senses: Contemporary Orthodox Christian Spirituality in Practice, edited by anthropologist Sonja Luehrmann, aims to “describe the workings of prayer in a tradition where hierarchies and prescriptions matter but where they are deployed through flexible and highly personal relationships” (p.12). In doing so, the authors of the chapters argue that living ‘the perfect Orthodox’ life is made both possible and difficult through the everyday interactions that people develop during their prayers. Hence, what people hear, see, and say even when they privately pray can be considered continuous relational milieux for negotiating and determining the ‘right’ ethical norms of the Christian Orthodox tradition.